(untitled) (Journal of Economic Research & Business Administration, 2023)
The minimum level of state support in Kazakhstan does not allow agricultural enterprises to intensively update equipment and technologies due to a low level of profitability, even taking into account state support. The high level of competition in agriculture forces agricultural producers to make every effort and use every opportunity to ensure the production of competitive products. The remaining financial resources are insufficient to ensure normal reproduction, and only state support allows agricultural enterprises to acquire the minimum necessary assets. The main goal of the article is to make a literature review on the innovation development in agriculture and identify factors impacting it. The authors emphasized the current problems and proposed innovative improvements to the current state of agriculture. The low level of education of farmers and lack of a regional knowledge transfer system together with the production and financing problems does not allow the development of innovative agriculture. Methods of statistical data analysis, literature analysis, state policy review, systematic approach, content analysis, and comparison were the methodological research tools. A systematic approach allows identifying common system properties and qualitative characteristics of elements of an innovation system. Content analysis compares literature studies. Statistical data analysis gives a visual picture of innovation related information for a period. Literature and state policy analysis enrich existing knowledge and research gaps for influencing agricultural innovations determinants. Key factors affecting the development of innovative processes in agriculture are the level of financial resources of organizations, the level of motivation to innovate, and the ability of organizations to create innovations or replicate innovations that have already been created. In our opinion, the state should organize research or project calls involving all necessary stakeholders where the implementation point is agribusiness, as innovation requires collaboration, ideation, implementation, and value creation. Currently, state research calls are organized separately for research not necessarily involving end users and implementation and commercialization of innovative ideas, which are not always interesting for agricultural producers. Key words: innovation, agricultural sector, entrepreneurship, agricultural policy, Kazakhstan.